Модификация автоматизированного рабочего места в ИРБИС для целей межбиблиотечного абонемента и доставки документов (Библиосфера)
The authors consider the issue of interlibrary loan automation in the State Public Scientific Technical Library of Siberian Branch of the Russian Academy of Sciences (SPSL SB RAS). Particularly the innovations introduced in 2007-2009 are described.